The impact of prolonged exercise in a cold environment upon cardiac function - Shave, R.; Dawson, E.; Whyte, G.; George, K.; Nimmo, M.; Layden, J.; Collinson, P.; Gaze, D. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of the present study was to examine the impact of cold exposure coupled with prolonged exercise upon postexercise left ventricular (LV) function and markers of myocardial damage. METHODS: colon; Eight highly trained male athletes (mean +/- SD; age: 28.2 +/- 8.8 yr; height: 1.78 +/- 0.07 m; body mass: 74.9 +/- 7.6 kg; VO2max: 65.6 +/- 7.0 mL x kg(-1) x min(-1)) performed two 100-mile cycle trials, the first in an ambient temperature of 0 degrees C, the second in an ambient temperature of 19 degrees C. Echocardiographic assessment was completed and blood samples drawn before, immediately postexercise, and 24-h postexercise. Left ventricular systolic (stroke volume [SV], ejection fraction [EF], and systolic blood pressure/end systolic volume ratio [SBP/ESV]) and diastolic (early [E] to late [A] filling ratio [E:A]) parameters were calculated. Serum was analyzed for creatine kinase isoenzyme MB (CK-MBmass) and cardiac troponin T (cTnT). cTnT was analyzed descriptively whereas other variables were assessed using two-way repeated-measures ANOVA. RESULTS: No significant change was observed in systolic function across time or between trials. A significant difference between trials was observed in E:A immediately after exercise (1.4 +/- 0.4 [19 degrees C] vs 1.8 +/- 0.3 [0 degrees C]) (P < 0.05). CK-MBmass was significantly elevated immediately after exercise in both trials (P < 0.05). Positive cTnT concentrations were observed in two subjects immediately after the 19 degrees C trial (0.012 microg x L(-1) and 0.034 microg x L(-1)). CONCLUSIONS: Cycling 100 miles in an ambient temperature of 19 degrees C is associated with an acute change in diastolic filling that is not observed after prolonged exercise at 0 degrees C. Prolonged exercise is associated with minimal cardiac damage in some individuals; it appears that this is a separate phenomenon to the change in diastolic filling.